2016
DOI: 10.1016/j.tjo.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of orbital fractures at a level I trauma center in a large metropolitan city

Abstract: Background/Purpose:Orbital fractures are a common facial fracture managed by multiple surgical specialties. Methods: A retrospective review of the electronic medical records of patients (age, 18–85 years) presenting to Northwestern Memorial Hospital and Northwestern Medical Faculty Foundation in Chicago, IL, USA with International Classification of Diseases, Ninth Revision codes for facial fractures or CPT (Current Procedural Terminology) codes for orbital fracture repair.Results:A review of the electronic med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 14 publications
5
24
1
1
Order By: Relevance
“…Our study showed that males in their fourth decade are the most common patients. Our male to female ratio was 3.3:1 which was comparable to previous studies reporting ratios of 2.3:1 in United States, 1 2.5:1 in Taiwan 2 , and 3.6:1 in Germany. 3 The most common racial group for orbital fractures were African Americans (63.6%).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our study showed that males in their fourth decade are the most common patients. Our male to female ratio was 3.3:1 which was comparable to previous studies reporting ratios of 2.3:1 in United States, 1 2.5:1 in Taiwan 2 , and 3.6:1 in Germany. 3 The most common racial group for orbital fractures were African Americans (63.6%).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, our study found no significant difference in orbital fractures when differentiating by side. This was in contrast to studies by Chiang et al in 2016 2 and Chi et al, 10 who found that left-sided orbital fractures were more common than right orbital fractures. The literature also reveals that individuals who are assaulted are much more likely to have left-sided fractures compared to those who had an orbital fracture by a different mechanism of injury.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations